MeerTRAP: 12 Galactic fast transients detected in a real-time, commensal MeerKAT survey. Issue 1 (9th March 2022) - Bezuidenhout, M C; Barr, E; Caleb, M; Driessen, L N; Jankowski, F; Kramer, M; Malenta, M; Morello, V; Rajwade, K; Sanidas, S; Stappers, B W; Surnis, M
ABSTRACT: MeerTRAP is a real-time untargeted search project using the MeerKAT telescope to find single pulses from fast radio transients and pulsars. It is performed commensally with the MeerKAT large survey projects (LSPs), using data from up to 64 of MeerKAT's 13.96 m dishes to form hundreds of coherent beams on sky, each of which is processed in real time to search for millisecond-duration pulses. We present the first 12 Galactic sources discovered by MeerTRAP, with DMs in the range of 33–381 pc cm −3 . One source may be Galactic or extragalactic depending on the Galactic electron density model assumed. Follow-up observations performed with the MeerKAT, Lovell, and Parkes radio telescopes have detected repeat pulses from 7 of the 12 sources. Pulse periods have been determined for four sources. Another four sources could be localized to the arcsecond-level using a novel implementation of the tied-array beam localization method.